INCULTURATION: PROSPECTS AND PROBLEMS - Thottakara, Augustine (Journal of Dharma, 1999)
Journal of Dharma is completing next year - in 2000- twenty-five years of its service to world religions. All these years the Journal, true to its professed policies and proposed ideals, promoted and propagated interreligious dialogue, universal brotherhood humanity and comparative study of religions; provided a forum for scholars from different traditions to share their views, insights and experience of religion and spirituality in relation to the other religious traditions of the world; helped seekers of truth to situate themselves in the multi-religious context of today and to appreciate the values and merits of other faiths; tried to seek and find God's revelation and presence, his power and grace in all religious traditions; encouraged the common endeavour of all religious persons to discover God's goodness manifested through different peoples in different times, in different scriptures and in the genuine religious traditions; pursued to encourage scholars to discuss and debate creatively the issues that vex humanity in its search for. abiding peace and happiness; tried to tell seekers of perfection that truth, goodness and sanctity are not monopoly of one religion and that if the almighty and omniscient God in his inscrutable providence and unsurpassed love and mercy deigns to manifest himself in various ways, in different cultures, religious traditions and among different peoples, the insignificant, little and limited humans have no right to question him; endeavoured to exhort the pilgrims of faith that seeking God and his goodness also in the scriptures of other religions, traditions and spiritual paths and in the lives and teachings of great spiritual persons can be beneficial to their own spiritual growth; but at the same time insisted that all religions are not the same, and that the content of faith transmitted through scriptures, traditions and official teachings of each religion has to be different and the commitment to this faith is to be firm.